Implementation of The Analytical Hierarchy Process (AHP) Method in The Laptop Election Decision Support System for Students and Community in Medan City - Abdillah, Abdillah (ZERO: Jurnal Sains, Matematika dan Terapan, 2021)
The development of an increasingly fast and instant era in this millennial era, makes electronic devices, especially laptops, also experience very fast and extensive development. The capacity of a laptop is closely related to the price of a laptop, if the capacity of the laptop is higher, the price of the laptop will also be higher, and vice versa if the capacity of the laptop is lower, the price of the laptop will also be lower. each laptop offers different features of each type and gives each type a unique look and shape. This is what makes students and the public confused about which laptop to choose according to their wishes and the money budget they have so that they don't make the wrong choice in determining the type of laptop that students and the community want later. On this basis, a study was made that is used in making decisions on laptop selection using the Analytical Hierarchy Process (AHP) method. This research was conducted to find out how the decision support system in choosing a laptop that suits the needs and economic conditions for students and the community.